Romantyczne tropy późnej nowoczesności - Artwińska, Anna (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
The article discusses the book entitled Romantyzm i nowoczesność (Kraków 2009), edited by Michał Kuziak in which the authors examine a possibility of an application of modern methodological propositions for an analysis of Romanticism in literature. The reviewer presents and briefly discusses each of the articles contained in the book, focusing particularly on the extent to which individual articles correspond to the main assumptions of the volume. Thus, the reviewer provides the reader with an analysis of the concepts of modernity and Romanticism presented by the authors, but also points out convergence points, interceptions and dependencies occurring between them. The volume, presenting novel interpretations and approaches to individual literary works, methodological reflections and studies on selected problems in aesthetics and Romantic ideology, has been critically acclaimed. The reviewer recommends the book as an interesting piece of writing not only for researchers in the history of the literature of the nineteenth century, but also for those studying culture and for theoreticians of narrative discourse.